Chemical Underpinning of the Tea Bag Index: An Examination of the Decomposition of Tea Leaves. (3rd January 2020) - Duddigan, Sarah; Shaw, Liz J.; Alexander, Paul D.; Collins, Chris D.
Abstract : Decomposition is a key flux of terrestrial carbon to the atmosphere. Therefore, gaining a better understanding of how plant litter decomposes in soil, and what governs this process, is vital for global climate models. The Tea Bag Index (TBI) was introduced by Keuskamp et al. (2013) as a novel method for measuring litter decomposition rate and stabilisation. The TBI uses two types of tea bags representing fast (green tea) and slow (rooibos tea) decomposition substrates as standardised litter bags. To date, the TBI method has been used in over 2000 locations across the globe. However, before now, there has been no information on how the composition of the tea leaves change during incubation. These data are crucial in determining the validity of the use of the TBI method globally, to ensure the tea leaves decompose in a way that is representative of so-called "native" litters. To provide chemical underpinning of the TBI method, a laboratory incubation of the tea bags was conducted with destructive sampling at 0, 7, 14, 21, 28, 35, 42, 49, 56, 63, 70, 77, 84, and 91 d. The incubated tea was analysed for total C and N. In addition, C was characterised as alkyl, O-alkyl, aromatic, or carbonyl C using solid-state 13 C nuclear magnetic resonance spectroscopy with cross-polarization and magic angle spinning (CPMAS NMR). The results suggest that changes in carbon in both tea types are comparable to other litter studies, with a net decrease in total C and relative proportion of O-alkyl C fraction, which contains carbohydrates and cellulose. We conclude that the decomposition of tea leaves in the bags used in the TBI is representative of other litters.